Paralomis birsteini Macpherson 1988 ... - Ahyong, Shane T.; Dawson, Elliot W. (Zenodo, 2006)
Paralomis birsteini Macpherson, 1988 (Figs. 5, 6) Paralomis spectabilis.—Birstein & Vinogradov, 1967: 390, figs. 1, 2— Kirkwood, 1984: 37, fig. 45 [map only].— Tkachuk, 1985: 1733 –1734, figs. A, B.— Zaklan, 2002: 773 [Ross Sea records] [not P. spectabilis Hansen, 1908]. Paralomis birsteini Macpherson, 1988a: 72 –74, figs. 4, 5a–e [type locality: Scott Island, Ross Sea, Antarctica, 67°29’S, 179°55’W].— Arana & Retamal, 1999: 101 [Bellingshausen Sea records].— Stevens, 2004: 6, 7 [part]. Neolithodes brodiei.— Thatje & Lörz, 2005: 335 [NIWA 3432 only; not N. brodiei Dawson & Yaldwyn, 1970]. Material examined. NIWA 3432, ovigerous female (cl 75.0, cw 72.9 mm), Balleny Seamount, 65°28.53–28.97’S, 161°02.88–02.75’E, 760– 750 m, TAN0402/269, RV Tangaroa, 7 Mar 2004; NIWA 24217, 1 male (cl 79.4 mm, cw 76.4 mm), near Scott I., 67°21.01–21.02’S, 179°52.68–52.34’W, 540–600 m, sled tow, TAN0602/394, 6 Mar 2006; NIWA 23842, 1 male (cl 41.4 mm, cw 40.7 mm), 1 female (cl 35.2 mm, cw 32.5 mm), both infected ... : Published as part of Ahyong, Shane T. & Dawson, Elliot W., 2006, Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura), pp. 45-68 in Zootaxa 1303 on pages 55-58, DOI: 10.5281/zenodo.173679 ...